Specific preparation of women for canoeing high level - Simon, M. (Training sprint canoeing. Progress in improving the physical, technical, tactical, psychological and nutritional preparation, 2015)
If we want to be good and successful coaches we never can stop learning - we always need to be open to the new ideas! How can we do this? We need to analyse and look at the implications of our work. Analyse ourselves. Analyse our athletes' performance and reaction to the training programmes. Analyse the competition. Analyse the opponents' performance. Analyse the technique! When we are watching a competition either live or on screen and try it to analyse it there are two things that we can see first; SPEED & TECHNIQUE Speed and technique are closely related to each other. We could say: the winner always has the best technique even if there are many winners with very different techniques.... We could say: the athlete with the best technique can win, so if I want to develop a Champion it is very simple; I need to teach my athlete the best technique and enter them into the next competition.... Obviously it is not that simple, it is a very complex process. Who can win? The strongest, the fastest, the fittest can win. Who can have the best technique? The strongest, the fastest, the fittest can have the best technique. What is the good technique? The good technique helps the athlete reach the necessary speed and to keep it on a good average during the race distance. Making a perfect preparation is a complex process, so we never can separate the key elements: Fitness & Technique are the background of the performance. Performance is the "product" and feedback of the preparation. These should be treated and developed as a unit. These constantly must interact with each other and affect the preparation plan. Through the next chapters I try to explain that what my principle is methodically, technically and tactically at the preparation of world class woman athletes.